Hollow metal dot matrix viscoelastic structure realized by utilizing viscous fluid in cavity and preparation method of hollow metal dot matrix viscoelastic structure

By introducing the combination of viscous fluid in the cavity and the metal matrix into the hollow metal lattice structure, the problem of aging failure of viscous elastomeric materials is solved, and a hollow metal lattice structure with elastic and viscous characteristics is realized, which is used for shock absorption and impact resistance, and the lattice structure library is expanded.

CN119532364AActive Publication Date: 2025-02-28HARBIN INST OF TECH
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202411459986.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-28
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

Existing viscoelastic materials are prone to aging and failure, and the study of metallized lattice materials lacks the exploration of viscoelastic structures, and fails to fully utilize the potential of additive manufacturing technology.

Method used

The combination of viscous fluid in the cavity and the metal matrix is ​​used to prepare hollow metal dot matrix structures through electroless plating and 3D printing technology to form a piston-shaped, spherical shell-shaped or composite dot matrix structure with springs. The fluid in the cavity provides viscoelasticity, and the elasticity of the metal matrix forms viscoelastic properties.

Benefits of technology

It realizes a dot matrix structure with both elastic and viscous characteristics, which is used for shock absorption and impact resistance, reduces the problem of aging and failure of polymer materials, and expands the current dot matrix structure library.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119532364A_ABST
    Figure CN119532364A_ABST
Patent Text Reader

Abstract

The invention discloses a hollow metal dot matrix viscoelastic structure achieved through viscous fluid in a cavity and a preparation method of the hollow metal dot matrix viscoelastic structure, and relates to the field of 3D printing and metalized dot matrix materials. The invention solves the problem that the existing viscoelastic material is easy to age and lose efficacy. Each dot matrix unit (A) comprises a hollow base body, and the hollow base body is metalized in a chemical plating mode to form a metal dot matrix unit; a plurality of lattice units (A) are connected with one another to obtain a hollow metal lattice structure, the hollow metal lattice structure is a piston-shaped or spherical shell-shaped cavity or a composite lattice structure with a spring, fluid in the cavity provides viscosity during compression, and the viscoelastic property is formed by the elasticity of a metal matrix; the method comprises the steps of 1, designing a lattice structure; and secondly, the hollow metal lattice structure is provided with a piston-shaped or spherical shell-shaped cavity and a spring structure, viscosity is provided by fluid in the cavity during compression, and the viscoelastic property is formed by the elasticity of the metal matrix. The shock absorber is used in shock-resistant and shock-absorbing environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of 3D printing and metallized lattice materials, and in particular to a hollow metal lattice viscoelastic structure realized by utilizing a viscous fluid in a cavity and a preparation method thereof. Background Art

[0002] Viscoelastic materials are widely used in the fields of machinery, chemical industry, construction, transportation, information, aerospace, etc. They can effectively absorb shock and vibration, thereby reducing energy transfer and noise generation. Viscoelasticity is an important characteristic of polymers, which gives polymers superior properties. Polymer materials show a combination of elasticity and viscosity. In the actual deformation process, viscosity and elasticity always coexist. When a polymer is subjected to force, the stress depends on both the deformation and the deformation rate, that is, it has both solid and liquid properties, and its mechanical behavior is between an ideal elastic body and an ideal viscous body. Viscoelasticity makes plastics have solid-like properties such as elasticity, strength, dimensional stability and liquid-like properties such as flow characteristics that change with time, temperature, load size and rate.

[0003] Compared with traditional metal structures, viscoelastic materials can reduce the weight of lattice sandwich structures with the same performance by up to 70%; their buffering and energy absorption capabilities and efficiency are better than those of honeycomb metal and foam metal; the specific strength and specific stiffness of metal lattice materials are much higher than those of traditional metal materials, and the load-bearing efficiency is greatly improved; lattice materials are used in space satellite solar energy structures to effectively improve the energy efficiency of solar energy per unit mass, which can reach 80-115W / kg.

[0004] Traditional viscoelastic materials are generally polymer materials, but these materials will degrade or cross-link due to external stimuli during processing, storage and use, resulting in aging and eventually failure problems such as embrittlement and cracking. If these materials can be replaced with metal lattices with viscoelastic geometric structures, aging and deformation problems caused by long-term loading can be effectively avoided.

[0005] At present, research on metallized lattice materials often focuses on improving strength and energy absorption rate, but lacks exploration of viscoelastic structures and has not fully tapped the potential of advanced additive manufacturing technology in material design.

[0006] In summary, existing viscoelastic materials are prone to aging and failure. Summary of the invention

[0007] The purpose of the present invention is to solve the problem that existing viscoelastic materials are prone to aging and failure, and further provide a hollow metal lattice viscoelastic structure realized by using a viscous fluid in a cavity and a preparation method thereof.

[0008] The technical solution of the present invention is:

[0009] A hollow metal lattice viscoelastic structure realized by using a viscous fluid in a cavity includes a plurality of lattice units, each of which includes a hollow substrate. The hollow substrate is metallized by chemical plating to form a metal lattice unit. The plurality of lattice units are interconnected to obtain a hollow metal lattice structure, which is a piston-shaped or spherical shell-shaped cavity or a composite lattice structure with a spring. When compressed, the fluid in the cavity provides viscosity, and the elasticity of the metal substrate forms viscoelastic properties.

[0010] The present invention also provides a method for preparing a hollow metal lattice viscoelastic structure realized by using a viscous fluid in a cavity, which comprises the following steps:

[0011] Step 1: Design the lattice structure;

[0012] Step 1: The software used is Siemens NX 2007 modeling software to draw the hollow matrix;

[0013] Step 1 and 2: Complete the base printing through light-curing 3D printing technology;

[0014] Step 13: metallization of the substrate is achieved by chemical plating; multiple lattice units are interconnected to form a lattice material;

[0015] Step 14: etching the substrate to obtain a hollow metal lattice structure;

[0016] Step 2: The hollow metal lattice structure has a piston-shaped or spherical shell-shaped cavity and a spring structure. When compressed, the fluid in the cavity provides viscosity, and the elasticity of the metal matrix forms viscoelastic properties.

[0017] Furthermore, the light curing means in steps one and two is: LCD screen light curing molding technology; its resolution is 0.05mm, the exposure time is 2s, and the printing platform lifting speed is 3mm / s.

[0018] Furthermore, the chemical plating described in steps 1 to 3 is a combination of traditional chemical plating and aluminum-induced chemical plating to obtain a pure metal coating.

[0019] Furthermore, step 1-3 further includes pretreatment of the substrate before chemical plating, and the pretreatment includes the following steps:

[0020] S1: Surface treatment:

[0021] Soak the printed substrate in acetone solvent at room temperature for 13-18 minutes, then rinse with distilled water;

[0022] S2: Alkaline degreasing:

[0023] The substrate is placed in a degreasing liquid, ultrasonically cleaned for 10 minutes to 20 minutes at room temperature, and then cleaned with distilled water to obtain an alkaline degreasing substrate material;

[0024] The degreasing liquid is composed of sodium hydroxide, sodium silicate, trisodium phosphate, sodium carbonate and distilled water, and 1L of the degreasing liquid contains 10g of sodium hydroxide, 3g of sodium silicate, 12g of trisodium phosphate and 8g of sodium carbonate respectively;

[0025] S3: Sensitization:

[0026] The base material after alkaline degreasing is placed in a 10g / L stannous chloride solution, soaked at room temperature for 6min to 8min, and then washed with distilled water;

[0027] S4: Activation:

[0028] The sensitized substrate material is placed in a 0.7 g / L palladium aqueous solution, immersed for 6 min to 10 min at room temperature, and then washed with distilled water to obtain a substrate suitable for chemical plating.

[0029] Preferably, when the chemical plating in step 1-3 is conventional chemical plating, the conventional chemical plating comprises the following steps:

[0030] Step 131: completing the pretreatment of the substrate;

[0031] Step 132: Prepare chemical plating solution according to the following ingredients: 25 g / L nickel sulfate, 50 g / L sodium pyrophosphate, 25 g / L sodium hypophosphite, 2.3 g / L sodium hydroxide, and distilled water;

[0032] Step 133: Perform chemical plating at 40-50°C.

[0033] Furthermore, after completing the conventional chemical plating, it is necessary to further implement aluminum induced chemical plating, which includes the following steps:

[0034] Step 14: Connecting the substrate coated with the metal layer after the conventional chemical plating operation to the aluminum foil to form a micro-battery;

[0035] Step 15: Utilize the electrode potential of aluminum foil to obtain reaction kinetics, and perform chemical plating in an aluminum induced chemical plating solution to replace the reducing agent containing P / B elements to obtain a pure metal coating. The types of pure metal coatings that can be obtained include one or more of nickel, iron, cobalt, chromium, tin and zinc.

[0036] Preferably, the aluminum induced chemical plating solution in step 15 is composed of nickel sulfate, triethanolamine and distilled water, the reaction temperature is room temperature of 20°C, and the pH value is 10-11.

[0037] Preferably, in steps one to four, a concentrated NaOH solution is used to etch the substrate.

[0038] Furthermore, it also includes fluid-solid coupling simulation and pure solid-state simulation of the prepared hollow metal lattice viscoelastic structure realized by using the viscous fluid in the cavity, and the fluids used in the simulation process include gas and liquid.

[0039] Compared with the prior art, the present invention has the following effects:

[0040] 1. The present invention is a structure that utilizes viscous fluid in the cavity to achieve the viscoelasticity of a hollow metal lattice. On the basis of the metallized hollow lattice, a viscoelastic cavity structure is designed. Combined with the elasticity of the metal itself, a lattice structure with both elastic and viscous characteristics is obtained. The structure can be used for shock absorption and impact resistance, and can reduce the problem of aging failure of polymer materials to a certain extent.

[0041] 2. The present invention introduces a new viscous structural primitive, which can be combined with an elastic structure to obtain a viscoelastic structure based on Maxwell, Kelvin or a composite model, further expanding the current lattice structure library.

[0042] 3. The present invention can obtain a structure that utilizes the viscous fluid in the cavity to achieve the viscoelasticity of the hollow metal lattice. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 It is a schematic diagram of the principle of utilizing the viscosity of the hollow metal lattice structure when the hollow metal lattice structure of the present invention is a spherical shell-shaped cavity;

[0044] Figure 2 It is a schematic diagram of the principle of utilizing the viscosity of the hollow metal lattice structure when the hollow metal lattice structure of the present invention is piston-shaped;

[0045] Figure 3 It is a schematic diagram of the principle of utilizing the viscosity of the hollow metal lattice structure when the hollow metal lattice structure of the present invention is a composite lattice structure with a spring; wherein the lattice unit A utilizes an elastic spring and a viscosity pot to realize viscoelasticity, and the model is a composite structure of a metal coating-resin matrix;

[0046] Figure 4 It is a unit of the lattice of spherical shell cavities. The unit uses elastic spherical shells and tiny pores to achieve viscoelasticity. The model is a metal-plated structure.

[0047] Figure 5 It is the stress feedback data obtained under constant deformation rate for the same structure in fluid-solid coupling simulation and pure solid structure simulation. DETAILED DESCRIPTION

[0048] Specific implementation method 1: Combination Figures 1 to 4To illustrate this embodiment, this embodiment includes a plurality of lattice units A, each of which includes a hollow substrate, and the hollow substrate is metallized by chemical plating to form a metal lattice unit; the plurality of lattice units A are interconnected to obtain a hollow metal lattice structure, which is a piston-shaped or spherical shell-shaped cavity or a composite lattice structure with a spring, and when compressed, the viscosity is provided by the fluid in the cavity, and the viscoelastic property is formed by the elasticity of the metal substrate.

[0049] When the hollow metal lattice structure in this embodiment is piston-shaped, its structural form is as follows: Figure 2 As shown, it includes a hollow cylindrical tank body A-1 and a piston rod body A-2, the piston rod body A-2 is inserted into the hollow cylindrical tank body A-1, and a gap is left between the outer edge of the cylinder of the piston rod body A-2 and the hollow cylindrical tank body A-1, and the gap is used for the piston rod body A-2 to discharge the medium (gas / liquid) from this gap when it is under pressure. In this process, the elastic element can absorb part of the instantaneous impact or vibration and store it as elastic energy, thereby reducing the peak intensity of the vibration and playing a role in cushioning. After being squeezed or stretched, the medium located in the hollow metal lattice structure flows in or out from the pores / gaps and generates friction with the pores / gaps, thereby consuming energy and further consuming the impact energy or the elastic energy stored in the spring. After being squeezed or stretched, the lattice structure recovers to its original shape with the help of the elastic part in the structure.

[0050] In actual use, the spherical shell cavity of this embodiment has a structural form as follows Figure 1 As shown, it is preferably an elliptical or spherical cavity, and the cavity is filled with medium. When the shape is elliptical, a discharge hole is respectively opened at both ends of the long axis direction, which is used to discharge the medium in time after being pressurized. When the shape is spherical, a discharge hole is opened at the upper part. And multiple elliptical or spherical cavities are connected to each other in four directions of up, down, left, and right.

[0051] When the hollow metal lattice structure of this embodiment is a composite lattice structure with a spring, its structural form is as follows: Figure 3 As shown, it includes a four-way tube body A-3 and a spring A-4. The four directions of the four-way tube body A-3 are inserted with adjacent four-way tube bodies A-3, and springs A-4 are mounted on two adjacent plug-in parts. The plug-in parts can be separated without being separated when the elastic potential energy of the spring A-4 is released, and the plug-in parts can be further plugged in with the spring when an external force is applied.

[0052] Specific implementation method 2: Combination Figure 1 This embodiment is described. The method for preparing a hollow metal lattice viscoelastic structure realized by using a viscous fluid in a cavity as described in claim 1 comprises the following steps:

[0053] Step 1: Design the lattice structure;

[0054] Step 1: The software used is Siemens NX 2007 modeling software to draw the hollow matrix;

[0055] Step 1 and 2: Complete the base printing through light-curing 3D printing technology;

[0056] Step 13: metallization of the substrate is achieved by chemical plating; a plurality of lattice units A are interconnected to form a lattice material;

[0057] Step 14: etching the substrate to obtain a hollow metal lattice structure;

[0058] Step 2: The hollow metal lattice structure has a piston-shaped or spherical shell-shaped cavity and a spring structure. When compressed, the fluid in the cavity provides viscosity, and the elasticity of the metal matrix forms viscoelastic properties.

[0059] This embodiment provides a method for preparing a hollow metal lattice structure, which is specifically implemented as follows:

[0060] In step 1, the structural design is completed using Siemens NX 2007 modeling software and processed using slicing software. The designed structure is a lattice unit obtained by combining a sticky pot and a spring structure;

[0061] In step 1 and 2, the model sliced ​​in step 1 is printed with a light-curing 3D printer, with a resolution (layer thickness) of 0.05 mm, an exposure time of 2 s, and a printing platform lifting speed of 3 mm / s to obtain a resin matrix;

[0062] The size of a single dot matrix unit in steps 1 and 3 is 4*4*4mm 3 , a plurality of lattice units constitute a lattice material;

[0063] Finally, the resin matrix is ​​etched to obtain a metal lattice structure with viscoelastic cavities.

[0064] In addition, in the actual practice of the present invention, as an alternative, the design mechanism of the lattice unit no longer adopts the structure of a sticky pot + spring, but uses a spherical shell with holes to realize the combination of a sticky and elastic structure. It is also possible not to consider etching the resin matrix in the design stage, and not to perform etching after chemical plating is completed, and directly obtain a metal plating layer-resin composite lattice structure.

[0065] In addition, the plating layer is no longer metallic nickel, but one or more of iron, cobalt, chromium, tin and zinc.

[0066] Specific implementation method three: Combination Figures 1 to 4To illustrate this embodiment, the light-curing means in steps one and two of this embodiment is: LCD screen light-curing molding technology; its resolution is 0.05mm, the exposure time is 2s, and the printing platform lifting speed is 3mm / s.

[0067] In this way, reasonable light curing parameters are conducive to ensuring the printing quality, ensuring the integrity of the printed structure, and ensuring that the wall thickness, joints, etc. are uniform and stable. Other components and connection relationships are the same as those in the first or second specific implementation.

[0068] Specific implementation method four: Combination Figures 1 to 4 To illustrate this embodiment, the chemical plating described in steps 1 and 3 of this embodiment is a combination of traditional chemical plating and aluminum induced chemical plating to obtain a pure metal coating.

[0069] In this way, compared with the traditional chemical plating method, the pure metal coating obtained by the aluminum induction method has reduced brittleness and better toughness due to the absence of interference from the non-metallic element P. The other components and connection relationships are the same as any one of the specific embodiments one to three.

[0070] Specific implementation method five: Combination Figures 1 to 4 To illustrate this embodiment, step 1 to step 3 of this embodiment further includes pretreatment of the substrate before chemical plating, and the pretreatment includes the following steps:

[0071] S1: Surface treatment:

[0072] Soak the printed substrate in acetone solvent at room temperature for 13-18 minutes, then rinse with distilled water;

[0073] S2: Alkaline degreasing:

[0074] The substrate is placed in a degreasing liquid, ultrasonically cleaned for 10 minutes to 20 minutes at room temperature, and then cleaned with distilled water to obtain an alkaline degreasing substrate material;

[0075] The degreasing liquid is composed of sodium hydroxide, sodium silicate, trisodium phosphate, sodium carbonate and distilled water, and 1L of the degreasing liquid contains 10g of sodium hydroxide, 3g of sodium silicate, 12g of trisodium phosphate and 8g of sodium carbonate respectively;

[0076] S3: Sensitization:

[0077] The base material after alkaline degreasing is placed in a 10g / L stannous chloride solution, soaked at room temperature for 6min to 8min, and then washed with distilled water;

[0078] S4: Activation:

[0079] The sensitized substrate material is placed in a 0.7 g / L palladium aqueous solution, immersed for 6 min to 10 min at room temperature, and then washed with distilled water to obtain a substrate suitable for chemical plating.

[0080] In this way, after immersion, palladium atoms are attached to the resin matrix, and the subsequent chemical plating will be carried out on these palladium atoms. The other components and connection relationships are the same as any one of the specific embodiments 1 to 4.

[0081] Specific implementation method six: Combination Figures 1 to 4 To illustrate this embodiment, when the chemical plating in step 1 to step 3 of this embodiment is conventional chemical plating, the conventional chemical plating includes the following steps:

[0082] Step 131: completing the pretreatment of the substrate;

[0083] Step 132: Prepare a chemical plating solution according to the following ingredients: 25 g / L nickel sulfate, 50 g / L sodium pyrophosphate, 25 g / L sodium hypophosphite, 2.3 g / L sodium hydroxide, and distilled water (distilled water is present as a solute);

[0084] Step 133: Perform chemical plating at 40-50°C for 2h.

[0085] Specific implementation method seven: Combination Figures 1 to 4 This embodiment is described. After completing the conventional chemical plating, aluminum induced chemical plating needs to be further performed. The aluminum induced chemical plating includes the following steps:

[0086] Step 14: Connecting the substrate coated with the metal layer after the conventional chemical plating operation to the aluminum foil to form a micro-battery;

[0087] Step 15: Utilize the electrode potential of aluminum foil to obtain reaction kinetics, and perform chemical plating in an aluminum induced chemical plating solution to replace the reducing agent containing P / B elements to obtain a pure metal coating. The types of pure metal coatings that can be obtained include one or more of nickel, iron, cobalt, chromium, tin and zinc.

[0088] In this way, compared with the traditional chemical plating method, the pure metal coating obtained by the aluminum induction method has reduced brittleness and better toughness due to the absence of interference from the non-metallic element P. The other components and connection relationships are the same as any one of the specific embodiments 1 to 6.

[0089] Specific implementation method eight: Combination Figures 1 to 4 To illustrate this embodiment, the aluminum induced chemical plating solution in step 15 of this embodiment is composed of nickel sulfate, triethanolamine and distilled water, the reaction temperature is room temperature of 20°C, and the pH value is 10-11. With such a configuration, the plating solution can ensure the smooth progress of chemical plating. The other components and connection relationships are the same as any one of the specific embodiments 1 to 7.

[0090] Specific implementation method nine: Combination Figures 1 to 4 To illustrate this embodiment, in step 1 to 4 of this embodiment, a concentrated NaOH solution is used to etch the substrate. In this way, the resin substrate will be etched hollow by etching, thereby obtaining a hollow metal micro-lattice structure. The other components and connection relationships are the same as any one of the specific embodiments 1 to 7.

[0091] Specific implementation method ten: Combination Figure 5 This embodiment is described. This embodiment also includes fluid-solid coupling simulation and pure solid-state simulation of the prepared hollow metal lattice viscoelastic structure realized by the viscous fluid in the cavity. The fluids used in the simulation process include gas and liquid. With such a setting, the effects of the lattice structure under different parameters can be directly compared through simulation means, reducing the number of experiments. The other components and connection relationships are the same as any one of the specific embodiments one to seven.

[0092] Combination Figures 1 to 5 It is explained that the present invention can adopt the following embodiments to verify the beneficial effects of the present invention:

[0093] Embodiment 1: A metal coating-resin composite viscoelastic lattice structure is completed by the following steps:

[0094] 1. Use Siemens NX 2007 modeling software to complete the structural design and obtain the following Figure 2 The structure shown is exported to the slicing software Vertical Cube Workshop in .stl file format, converted into .pm3 file format and imported into the light-curing 3D printer Anycubic Photon M3;

[0095] 2. Print according to the following parameters: resolution (layer thickness) is 0.05mm, normal exposure time is 2s, light off time is 0.5s, bottom exposure time is 23s, bottom layer number is 4, printing platform lifting speed is 3mm / s, lifting height is 6mm, and retraction speed is 4mm / s;

[0096] 3. After successful printing, remove the model from the printing platform, clean it with alcohol, and remove the resin support after curing with ultraviolet light to obtain the resin matrix.

[0097] 4. Perform chemical plating on the substrate according to the following steps:

[0098] a) Surface treatment: Soak the printed structure in acetone solvent at room temperature for about 15 minutes, and then wash it with distilled water;

[0099] b) Alkaline degreasing: placing the substrate in a degreasing liquid, ultrasonically cleaning it at room temperature for 10 to 20 minutes, and then cleaning it with distilled water to obtain a base material after alkaline degreasing; the degreasing liquid is composed of sodium hydroxide, sodium silicate, trisodium phosphate, sodium carbonate and distilled water, and 1L of the degreasing liquid contains 10g of sodium hydroxide, 3g of sodium silicate, 12g of trisodium phosphate and 8g of sodium carbonate respectively;

[0100] c) Sensitization: Place the base material after alkaline degreasing in a 10g / L stannous chloride solution, soak for 6min to 8min at room temperature, and then wash with distilled water;

[0101] d) Activation: placing the sensitized substrate material in a 0.7 g / L palladium aqueous solution, soaking it at room temperature for 6 min to 10 min, and then washing it with distilled water to obtain a substrate suitable for chemical plating;

[0102] e) Plating: Prepare a chemical plating solution according to the following ingredients: nickel sulfate (25 g / L), sodium pyrophosphate (50 g / L), sodium hypophosphite (25 g / L), sodium hydroxide (2.3 g / L), and distilled water, and carry out chemical plating at 40-50°C.

[0103] f) connecting the plated substrate with the aluminum foil by a wire to form a loop and placing the substrate in an aluminum induced chemical plating solution to further obtain a pure nickel coating on the chemical nickel plating layer;

[0104] g) After cleaning, a lattice structure with viscoelasticity is obtained.

[0105] Embodiment 2: A hollow metal viscoelastic lattice structure is completed by the following steps:

[0106] 1. Use Siemens NX 2007 modeling software to complete the structural design and obtain the following Figure 3 The structure shown is exported to the slicing software Vertical Cube Workshop in .stl file format, converted into .pm3 file format and imported into the light-curing 3D printer Anycubic Photon M3;

[0107] 2. Print according to the following parameters: resolution (layer thickness) is 0.05mm, normal exposure time is 2s, light off time is 0.5s, bottom exposure time is 23s, bottom layer number is 4, printing platform lifting speed is 3mm / s, lifting height is 6mm, and retraction speed is 4mm / s;

[0108] 3. After successful printing, remove the model from the printing platform, clean it with alcohol, and remove the resin support after curing with ultraviolet light to obtain the resin matrix.

[0109] 4. Perform chemical plating on the substrate according to the following steps:

[0110] a) Surface treatment: Soak the printed structure in acetone solvent at room temperature for about 15 minutes, and then wash it with distilled water;

[0111] b) Alkaline degreasing: placing the substrate in a degreasing liquid, ultrasonically cleaning it at room temperature for 10 to 20 minutes, and then cleaning it with distilled water to obtain a base material after alkaline degreasing; the degreasing liquid is composed of sodium hydroxide, sodium silicate, trisodium phosphate, sodium carbonate and distilled water, and 1L of the degreasing liquid contains 10g of sodium hydroxide, 3g of sodium silicate, 12g of trisodium phosphate and 8g of sodium carbonate respectively;

[0112] c) Sensitization: Place the base material after alkaline degreasing in a 10g / L stannous chloride solution, soak for 6min to 8min at room temperature, and then wash with distilled water;

[0113] d) Activation: placing the sensitized substrate material in a 0.7 g / L palladium aqueous solution, soaking it at room temperature for 6 min to 10 min, and then washing it with distilled water to obtain a substrate suitable for chemical plating;

[0114] e) Plating: Prepare a chemical plating solution according to the following ingredients: nickel sulfate (25 g / L), sodium pyrophosphate (50 g / L), sodium hypophosphite (25 g / L), sodium hydroxide (2.3 g / L), and distilled water, and carry out chemical plating at 40-50°C.

[0115] f) connecting the plated substrate with the aluminum foil by a wire to form a loop and placing the substrate in an aluminum induced chemical plating solution to further obtain a pure nickel coating on the chemical nickel plating layer;

[0116] g) etching the substrate with alkaline solution to obtain a hollow metal lattice with viscoelastic properties.

[0117] 5. The structure was simulated by fluid-solid coupling and pure solid structure respectively. The results are as follows: Figure 4 As shown, the results show that after the introduction of air fluid, the feedback stress of the lattice structure under the same strain conditions increases, which means that compared with the vacuum state, the air fluid produces a viscous effect, that is, under faster extrusion, the viscous fluid produces greater resistance. This can further illustrate that after the introduction of air fluid, the structure's ability to resist external deformation and energy consumption are improved.

[0118] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A hollow metal lattice viscoelastic structure realized by using a viscous fluid in a cavity, characterized in that: It includes a plurality of lattice units (A), Each lattice unit (A) comprises a hollow substrate, and the hollow substrate is metallized by chemical plating to form a metal lattice unit; A plurality of lattice units (A) are interconnected to obtain a hollow metal lattice structure, which is a piston-shaped or spherical shell-shaped cavity or a composite lattice structure with a spring. When compressed, the viscosity is provided by the fluid in the cavity, and the viscoelastic property is formed by the elasticity of the metal matrix.

2. A method for preparing a hollow metal lattice viscoelastic structure realized by using a viscous fluid in a cavity as claimed in claim 1, characterized in that: It includes the following steps: Step 1: Design the lattice structure; Step 1: The software used is Siemens NX 2007 modeling software to draw the hollow matrix; Step 1 and 2: Complete the base printing through light-curing 3D printing technology; Step 13: metallization of the substrate is achieved by chemical plating; a plurality of lattice units (A) are interconnected to form a lattice material; Step 14: etching the substrate to obtain a hollow metal lattice structure; Step 2: The hollow metal lattice structure has a piston-shaped or spherical shell-shaped cavity and a spring structure. When compressed, the fluid in the cavity provides viscosity, and the elasticity of the metal matrix forms viscoelastic properties.

3. The preparation method according to claim 2, characterized in that: The light curing method in steps one and two is: LCD screen light curing molding technology; its resolution is 0.05mm, the exposure time is 2s, and the printing platform lifting speed is 3mm / s.

4. The preparation method according to claim 3, characterized in that: The chemical plating described in step 1 to step 3 is a combination of traditional chemical plating and aluminum induced chemical plating to obtain a pure metal coating.

5. The preparation method according to claim 4, characterized in that: Step 13: Before chemical plating, the substrate is pretreated, and the pretreatment includes the following steps: S1: Surface treatment: Soak the printed substrate in acetone solvent at room temperature for 13-18 minutes, then rinse with distilled water; S2: Alkaline degreasing: The substrate is placed in a degreasing liquid, ultrasonically cleaned for 10 minutes to 20 minutes at room temperature, and then cleaned with distilled water to obtain an alkaline degreasing substrate material; The degreasing liquid is composed of sodium hydroxide, sodium silicate, trisodium phosphate, sodium carbonate and distilled water, and 1L of the degreasing liquid contains 10g of sodium hydroxide, 3g of sodium silicate, 12g of trisodium phosphate and 8g of sodium carbonate respectively; S3: Sensitization: The base material after alkaline degreasing is placed in a 10g / L stannous chloride solution, soaked at room temperature for 6min to 8min, and then washed with distilled water; S4: Activation: The sensitized substrate material is placed in a 0.7 g / L palladium aqueous solution, immersed for 6 min to 10 min at room temperature, and then washed with distilled water to obtain a substrate suitable for chemical plating.

6. The preparation method according to claim 5, characterized in that: When the chemical plating in step 1-3 is conventional chemical plating, the conventional chemical plating includes the following steps: Step 131: completing the pretreatment of the substrate; Step 132: Prepare chemical plating solution according to the following ingredients: 25 g / L nickel sulfate, 50 g / L sodium pyrophosphate, 25 g / L sodium hypophosphite, 2.3 g / L sodium hydroxide, and distilled water; Step 133: Perform chemical plating at 40-50°C.

7. The preparation method according to claim 6, characterized in that: After completing the traditional chemical plating, it is necessary to further implement aluminum induced chemical plating, which includes the following steps: Step 14: Connecting the substrate coated with the metal layer after the conventional chemical plating operation to the aluminum foil to form a micro-battery; Step 15: Utilize the electrode potential of aluminum foil to obtain reaction kinetics, and perform chemical plating in an aluminum induced chemical plating solution to replace the reducing agent containing P / B elements to obtain a pure metal coating. The types of pure metal coatings that can be obtained include one or more of nickel, iron, cobalt, chromium, tin and zinc.

8. The preparation method according to claim 7, characterized in that: The aluminum induced chemical plating solution in step 15 is composed of nickel sulfate, triethanolamine and distilled water, the reaction temperature is room temperature of 20°C, and the pH value is 10-11.

9. The preparation method according to claim 8, characterized in that: In step 1-4, a concentrated NaOH solution is used to etch the substrate.

10. The preparation method according to claim 2 or 9, characterized in that: It also includes fluid-solid coupling simulation and pure solid-state simulation of the prepared hollow metal lattice viscoelastic structure realized by using viscous fluid in the cavity, and the fluids used in the simulation process include gas and liquid.

Citation Information

Patent Citations

  • Hollow metal ball structure sandwich panel and manufacturing method thereof

    CN103921494A

  • Linked arrays of void cells

    CN105531497A

  • Lattice metal composite structure with nanometer core-shell structure and preparation method thereof

    CN106866896A

  • Preparation method of spherical unit cell ultralight foam metal material

    CN108118173A

  • Lattice metal / silicon rubber impact-protection and energy-absorbing material and preparation method thereof

    CN108189496A